Original paperBee pollen allergy in Polish beekeepers and their families - Basista, Katarzyna; Filipek, Barbara; Sodzawiczny, Krystian (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
Introduction: A bee pollen allergy is rare and often confused with a pollen allergy. The possibility of inducing an allergy in pollen allergic patients by bee pollen is still controversial. Aim : To determine the prevalence of bee pollen allergy in beekeepers and their families and its possible association with other conditions. Material and methods: The questionnaire study was carried out on 493 Polish beekeepers. The questionnaire was based on the current literature and touched on several aspects of a bee products allergy. Results : Only 19.4% (493 from 2540 questionnaires sent) of questionnaires were returned by 15 October 2011. From the total group, only 2 beekeepers reported adverse reactions after bee pollen ingestion. They presented only minor reactions. From 493 beekeepers, 43 responders reported other allergies. From that group, no one reported a concomitant bee pollen allergy. Additionally, beekeepers reported only 22 cases of bee pollen intolerance among their customers and in family members a bee pollen allergy occurred in 0.56% of cases. Conclusions : This preliminary study provides some new aspects on the bee pollen allergy. The thesis that a bee pollen allergy is associated with the occurrence of proteins from bee saliva rather than the occurrence of anemophilous plant pollen should be evaluated in future studies.